Enhancement of optical and electrochemical properties via bottom-up assembly of binary oligomer system - Mondal, Prakash Chandra; Chhatwal, Megha; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Heterometallic, coordination-based, binary oligomer films were fabricated on SiOx-based solid substrates using successive layer-by-layer assembly of optically rich and redox-active polypyridyl complexes, Ru(pytpy)2·2PF6 (Ru-PT) and Os(pytpy)2·2PF6 (Os-PT) (where pytpy = 4′-pyridyl-2,2′:6′,2″-terpyridyl). The individual oligomer chains comprised alternating Ru-PT and Os-PT units connected via Cu2+, Pd2+, Ag+, Fe2+, Co2+, or Zn2+ metallo-linkers. The growth and properties of the oligomer films were monitored in detail by UV-vis spectroscopy and cyclic voltammetry. The films exhibited a linear growth upon addition of the successive building blocks, with a joint grafting density of 3.9-5.0 × 1014 metallo-ligands/cm2 for the final oligomer films (10 layers), corresponding to a characteristic area of 2.0-2.5 nm2/oligomer. The only exception was the Pd2+-linked film on glass that showed an exponential growth, which, however, could also be changed to the linear mode by the introduction of a conductive substrate. The combination of two different functional molecular units in the oligomer chains resulted in enhancement of the optical window and in an increase in the number of the available redox states as compared to the analogous single component assemblies.